In its very early phases, COVID-19 shifts the associations between alcohol consumption and psychological symptoms in young adults - Karina Janson; Arun L.W. Bokde; Sylvane Desrivières; Hugh Garavan; Penny Gowland; Antoine Grigis; Andreas Heinz; Jean-Luc Martinot; Marie-Laure Paillère Martinot; Eric Artiges; Dimitri Papadopoulos Orfanos; Tomáš Paus; et al. (European Psychiatry)
Abstract Background The COVID-19 pandemic has impacted various aspects of daily life, leading to increased psychological symptoms and changes in alcohol use, yet little is known about their specific interactions, particularly early stages during the pandemic. We examined the relationship between psychological symptoms and alcohol-related behaviors associated with COVID-19, and determined whether associations shifted already early during the pandemic and whether changes in psychological symptoms from the pre- to during COVID-19 impacted changes in alcohol consumption.